The Design and Fabrication of NOS~ ciku Harvester - Abdul Karim, Mohd Nordin (1988)
A device for harvesting ciku has been successfully constructed. It has a system enabling the fruit to be measured and harvested intact and with ease. It can be modified to harvest other fruits requiring a horizontal cutting motion due to their orientation on the tree.